2017
DOI: 10.5130/ajceb.v17i2.5319
|View full text |Cite
|
Sign up to set email alerts
|

Determining Success Criteria and Success Factors for International Construction Projects for Malaysian Contractors

Abstract: The success of international construction projects is fraught with various challenges such as competitiveness, lack of resources, versatile global economy, and specific conditions in the host country. Malaysian contractors have been venturing into global construction market since early 1980s. However, their venturing was not successful all the time. The number of international projects awarded to Malaysian contractors has reduced drastically during the past decade. Taking advantage of this experience, this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…The uncertainty that was subsequently generated in the international market has been reflected in the statistics published by the Engineering News Record (ENR 2017), according to which international revenues of the 250 largest international contractors from projects abroad reached $468.12 billion in 2016 compared to $ 501.14 billion in 2015. Despite this uncertainty, there are different reasons why construction companies have expanded their business to international markets, such as national market saturation, the distribution of risk, or the use of opportunities abroad (Alashwal et al 2017). However, it must be taken into account that international projects involve more risks than projects carried out in the national market because they take place in environments characterized by political, economic, social, legal, and cultural differences that will affect the performance of engineering companies (CII 2013;Han et al 2007a;Javernick-Will and Scott 2010;Jin et al 2013;Park et al 2014).…”
Section: Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…The uncertainty that was subsequently generated in the international market has been reflected in the statistics published by the Engineering News Record (ENR 2017), according to which international revenues of the 250 largest international contractors from projects abroad reached $468.12 billion in 2016 compared to $ 501.14 billion in 2015. Despite this uncertainty, there are different reasons why construction companies have expanded their business to international markets, such as national market saturation, the distribution of risk, or the use of opportunities abroad (Alashwal et al 2017). However, it must be taken into account that international projects involve more risks than projects carried out in the national market because they take place in environments characterized by political, economic, social, legal, and cultural differences that will affect the performance of engineering companies (CII 2013;Han et al 2007a;Javernick-Will and Scott 2010;Jin et al 2013;Park et al 2014).…”
Section: Problem Statementmentioning
confidence: 99%
“…A study conducted by Hwang and Lim (2012) identified 32 key success factors in the context of construction in Singapore, in order to help foreign contractors that wanted to access this country, and noted that "the success of the construction project depends on a combination of factors related to the human being, factors related to the project, factors related to the management of the project, and even factors related to the external environment". In addition, Pal et al (2017) analyzed the success factors in relationship management in international engineering procurement and construction (IEPC) projects carried out by Chinese companies, and Alashwal et al (2017) identified the success factors of the internationalization of Malaysian contractors.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations